Uncertainty of Law Regarding Restitution as Legal Protection for Child Victims of Sexual Violence - Merry Aryanti; Suparno Suparno (Publikasi Indonesia, 2024)
This study examines the legal uncertainty related to the implementation of restitution as a form of legal protection for child victims of sexual violence. The issues raised include unclear regulations, complicated administrative procedures, and lack of support from law enforcement officers in the process of submitting and fulfilling restitution. These conditions often prevent victims from obtaining compensation that is their right according to court decisions that have permanent legal force. This study aims to analyze the legal uncertainty related to the implementation of restitution for child victims of sexual violence in Indonesia, identify obstacles in its implementation, and provide recommendations for improving the existing legal system to create better legal certainty. This study uses a normative legal method with a statute approach and a case approach. The results of the study indicate that legal uncertainty regarding restitution for child victims of sexual violence is caused by ambiguous regulations, inconsistencies between applicable regulations, and complicated administrative procedures. Support from law enforcement officers, especially public prosecutors, is often less than optimal in facilitating restitution applications by victims. In addition, limited socialization regarding victim rights exacerbates uncertainty in the implementation of the law. This study provides theoretical and practical implications in the development of criminal law and child protection. Theoretically, this study enriches the criminal law literature related to victims' rights and the implementation of restitution. Practically, the results of this study can be a reference for policy makers in formulating clearer and more implementable regulations. The proposed recommendations include simplifying administrative procedures, strengthening the role of prosecutors, and increasing the socialization of victims' rights to create a more responsive and equitable legal system.